Mindfulness Training for Healthy Aging: Impact on Attention, Well-Being, and Inflammation - Fountain-Zaragoza, Stephanie; Prakash, Ruchika Shaurya (Frontiers in Aging Neuroscience, 2017)
The growing interest in mindfulness interventions for use in aging samples has been met with promising evidence of cognitive, emotional, and physiological benefits. The purpose of this review is to provide an overview of the impact of mindfulness training on three areas of functioning in older adults: behavioral and neural correlates of attentional performance, psychological well-being, and systemic inflammation. We have previously proposed that mindfulness training is uniquely suited as a rehabilitative tool for conferring both cognitive and emotional benefits for older adults. Specifically, mindfulness training’s promotion of focused attention may mitigate the decline of attentional control abilities across late development and allow older adults to capitalize on their preserved emotion regulation abilities. Existing evidence points to some improvements in facets of attentional control in older adults, although some studies have shown no benefits in performance. Further, there is evidence of enhancements in both psychological and physical aspects of well-being, and accompanying improvements in systemic inflammation, following mindfulness training. The scientific investigation of mindfulness training is still relatively nascent, with only a limited number of studies, particularly randomized controlled trials utilizing active comparison conditions. It will be important for future research to incorporate placebo-controlled comparison groups to clearly establish the causal role of mindfulness practices in promoting holistic health in older adults.